Pengaruh Basis Krim Terhadap Penetrasi Kloramfenikol Menggunakan Kulit Mencit - Maria Dona Octavia; Sri Kartika Ayu; Auzal Halim (STIFARM Padang, 2012)
Absorption of active ingredients of topical preparations occur when the active substance is released from the carrier, then penetrate into deeper skin layers,into the capillaries and finally enter the bloodstream. This took place in passive diffusion. The aim of this study is to determine the influence of cream base type toward the penetration of chloramfenikol as the active ingredient. The examination done by using Franz diffusion cells vertical with miceskin as a membrane penetration.The resultsshowed that the 2ndformula was better than the 1st and 3rd formula in organoleptic, homogeneity, pH value, washed ability, and the spread of particle size.There are none of the formula caused iritation. The chloramfenikol quantitation measurement which done by using UV spectrophotometer, gave result 101.8 %, 99.8 %, 98.4 % for formula 1, 2, and 3. From thepenetration test showedthe 2nd formula has the best penetration which is 26.07 %.